2016
DOI: 10.2967/jnumed.115.165118
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-Specific Binding of Radiolabeled PEGylated GIRLRG Peptide: A Novel Agent for Targeting Cancers

Abstract: Cancer-specific targeting sparing normal tissues would significantly enhance cancer therapy outcomes and reduce cancer-related mortality. One approach is to target receptors or molecules that are specifically expressed on cancer cells. Peptides as cancer-specific targeting agents offer advantages such as ease of synthesis, low antigenicity, and enhanced diffusion into tissues. Glucose-regulated protein 78 (GRP78) is an endoplasmic reticulum stress chaperone that regulates the unfolded protein response and is o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 38 publications
1
12
0
Order By: Relevance
“…Our data demonstrate that TOF PET/MRI reconstruction results in higher SUV max measurements in physiological osseous structures as well as in lesions within the prostate, bones, and lymph nodes compared to non-TOF PET reconstructions. This is in concordance to preliminary data shown in an abstract by Mollard et al who also found higher SUV max in TOF reconstructions compared to non-TOF reconstructions in lesions in prostate patients with 18 F-choline [ 55 ] and is consistent with the findings of a simulation study of Mehranian et al [ 21 ].…”
Section: Discussionsupporting
confidence: 92%
“…Our data demonstrate that TOF PET/MRI reconstruction results in higher SUV max measurements in physiological osseous structures as well as in lesions within the prostate, bones, and lymph nodes compared to non-TOF PET reconstructions. This is in concordance to preliminary data shown in an abstract by Mollard et al who also found higher SUV max in TOF reconstructions compared to non-TOF reconstructions in lesions in prostate patients with 18 F-choline [ 55 ] and is consistent with the findings of a simulation study of Mehranian et al [ 21 ].…”
Section: Discussionsupporting
confidence: 92%
“…Since the intrinsic labeling does not alter the structure of the molecule and possesses fast identical physicochemical property to analytes, it can represent the pharmacokinetic behavior of the analytes precisely. Radiolabeling is commonly used in the studies of the in vivo absorption, distribution, metabolism, and excretion (ADME) processes of PEG [62,78,79], PEGylated small molecules [80], PEGylated peptides [81–83], PEGylated proteins [84–86], and PEGylated nanoparticles [10,87–93], which will be discussed in the following parts respectively.…”
Section: Bioanalytical Methods For Polyethylene Glycols and Pegylatedmentioning
confidence: 99%
“…For all in vivo studies, DTPA-PEG-control and DTPA-PEG-HVGGSSV peptide were labeled with 111 Indium. The labeling efficiency was optimized by trying different temperatures, buffers, and pH as described earlier [26]. The best yield was obtained by carrying out all reactions under absolute metal-free condition.…”
Section: Radiolabeling Of Peg Peptidesmentioning
confidence: 99%